Innovations in the foreign and security policy of the European Union after the Lisbon treaty - Novičić Žaklina (Međunarodni Problemi, 2010)
The article deals with institutional innovations introduced with Lisbon Treaty in the EU common foreign and security policy. The pillar structure of EU was abolished, but main features of intergovernmental decision-making procedures and unanimity would de facto remain. That is the main structural constrain of a single and bolder European outbreak an international scene. An novelty is the some kind of presidentialization (personalization) of the field in the new posts of President of European Council and the High Representative of the Union for Foreign Affairs and Security Policy. New procedures and structures are introduced also in a realm of Common Security and Defense Policy. A special hope of Eurocrats are put on the ongoing process of setting up new European External Action Serves as de facto new diplomatic service of the Union. However, there is the main paradox of the Lisbon arrangement in that it is supposed to confirm integration through foreign policy success at a same time when Europe is divided over a number of domestic as well as foreign policy issues, and all that at a time of the manifold global financial and economic crises.